Feasibility Analysis of Community Forest Ecotourism Potential in Tumpak Village, Pujut District, Central Lombok Regency - Sulaksono, Hendro; Sukardi, Lalu; Hadi, Islamul (Jurnal Biologi Tropis, 2024)
The Tumpak Village Community Forest Area has various potentials, with natural views as the main attraction. This research aims to determine the priority scale for developing this area through a feasibility level analysis using rules based on the Analysis of Operational Areas of Natural Tourist Attraction Objects (ADO-ODTWA). This research is quantitative and uses a survey method, with scoring analysis based on criteria in the ADO-ODTWA rules. Primary data was obtained through field observations, in-depth interviews, and distributing questionnaires. Meanwhile, secondary data was obtained through literature reviews, journal articles, books and geospatial data. The research results show that the Tumpak Village Community Forest area has a high level of feasibility and has the potential to be developed as ecotourism. Criteria for obtaining a high classification include ecotourism attractiveness, availability of accommodation, surrounding environmental conditions, supporting facilities, and availability of clean water. The criteria for the medium classification include accessibility, management and services that still need improvement, as well as marketing that is still limited. Management and development of this area can be carried out with a focus on managing potential tourist attractions and improving the required infrastructure. In addition, increasing accessibility requires support from the Regional Government of Central Lombok Regency to improve road infrastructure.